Acute breathlessness. Issue 8 (August 2015) - Davis, Tim
Acute breathlessness is a common presentation to primary care; it can range from asthma exacerbations to congestive cardiac failure. Being able to assess and manage acute breathlessness is an important skill within general practice. This article covers the general principles of first-line assessment and the management of breathlessness in primary care, focusing on respiratory causes. Specific causes of breathlessness are covered with cases to highlight key learning points.